ANALISIS PELAYANAN KEPENDUDUKAN DI KANTOR KECAMATAN KARANGAN KABUPATEN TRENGGALEK JAWA TIMUR - Devie Mahardikasari; Radjikan (CV Putra Publisher, 2023)
This study aims to determine population services in the Karangan District Office and the constraints faced in population services. This research uses a qualitative research type with a descriptive approach, which focuses on population services in the Karangan District Office. The research location was carried out at the Karangan District Office, Trenggalek Regency, East Java by collecting research data through direct observation then conducting interviews and taking documentation as evidence. Based on the results of research conducted on population services at the Karangan District Office, they have met service standards on indicators of conformity to requirements. Information regarding requirements and types of services has been provided widely through the website, the requirements provided have been adjusted to the needs in completing the service process. On the indicator of ease of procedure, ease of service has been given to a one-door system where the flow of document management services is very short and fast. On the speed indicator, the average time needed in the service process is around 5-10 minutes depending on the type of service and the completeness of the requirements. On the indicator of fairness of fees/tariffs in all types of services, there is no charge whatsoever. On the indicator of the ability of officers, it is necessary to increase the competency of service officers related to information technology. The indicators for the quality of infrastructure are sufficient, but there is a need for improvement, especially infrastructure that supports service processes such as air conditioning and computers. In the indicator for handling complaints, service users are still lacking in providing information on filling out the suggestion box and there is no standard operating procedure for handling this resulting in a lack of proper coordination regarding incoming complaints.